The effect of job satisfaction and workload on employee performance at PT Suri Tani Pemuka - Sahasrani, Fika; Oktavia, Eca; Eka Prasasti, Putri; Haryadi, Didit (Junal Ilmu Manajemen, 2024)
Organizations can achieve success through their resources, especially human resources. Therefore, employees become locomotors who contribute to the organization's success sustainably. Of course, only employees with optimal performance can achieve such success. However, to maximize employee performance, there must be a strategy to improve it. This study used an associative descriptive quantitative method with a population of 50 respondents drawn into samples using non-probability sampling and saturated sampling / total sampling methods. Data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis states that employee performance is influenced by employee job satisfaction, meaning that the higher the job satisfaction felt by employees, the higher employee performance. The second hypothesis states that workload shows no influence on employee performance. The third hypothesis is that employee performance is influenced by employee job satisfaction and workload, which can simultaneously improve employee performance. This research is expected to make theoretical contributions to the literature in this context, certainly in the context of human resource management.